2018
DOI: 10.1016/j.clim.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Immature myeloid cells in the tumor microenvironment: Implications for immunotherapy

Abstract: Various preclinical studies have demonstrated that the success of immunotherapeutic strategies in inhibiting tumor progression in animal models of Glioblastoma multiforme (GBM). It is also evident that tumor-induced immune suppression drastically impacts the efficacy of immune based therapies. Among the mechanisms employed by GBM to induce immunosuppression is the accumulation of regulatory T cells (Tregs) and Myeloid derived suppressor cells (MDSCs). Advancing our understanding about the pathways regulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 123 publications
(193 reference statements)
0
37
0
Order By: Relevance
“…In the present paper, we aim at the revision of pharmacological strategies that interfere with GAMs' function, i.e., cell recruitment at the tumor site, cell inflammatory activation and immune function, and the extracellular matrix remodeling promoted by GAM-secreted factors. For recent advances on the biology of MDSCs and Tregs in the glioblastoma microenvironment and their potential role as therapeutic targets, we refer the readers to other review articles [20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we aim at the revision of pharmacological strategies that interfere with GAMs' function, i.e., cell recruitment at the tumor site, cell inflammatory activation and immune function, and the extracellular matrix remodeling promoted by GAM-secreted factors. For recent advances on the biology of MDSCs and Tregs in the glioblastoma microenvironment and their potential role as therapeutic targets, we refer the readers to other review articles [20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…3e). These tumours are known to be highly infiltrated with myeloid cells, which may serve as an additional immunosuppressive mechanism preventing efficacy with ICI therapy 36,37 . Notably, these cancer types were also characterized by elevated IMS scores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously reported that glioma infiltrating MDSCs play a key role in inhibiting anti-tumor T-cell immune responses, thus promoting tumor progression 18 . The inhibitory immune-microenvironment in glioma is thought to contribute to the ineffectiveness of immunotherapies 31 . Novel therapeutics approaches that reverse the inhibitory microenvironment are essential to counteract these effects, and we propose that the inhibition of FYN within glioma cells could represent such a strategy.…”
Section: Discussionmentioning
confidence: 99%